New time-frequency method of harmonic signal extraction in chaotic secure communication system - WANG Er-fu; WANG Dong-qing; DING Qun (Tongxin xuebao)
after the time-frequency character analyses of the chaos,the noise and the harmonic signal,a new two-step extraction method of time-frequency was put forward,aimed to complement each other’s advantages and mutual fusion for wavelet multi-scale decomposition and empirical mode decomposition.The problem that the influence of the amplitude,frequency and noise energy on the extraction performance is also dissuced.Computer simulation verified that the method has high availability.